2014
DOI: 10.5665/sleep.3502
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Problems and Hospitalization for Self-Harm: A 15-Year Follow-Up of 9,000 Norwegian Adolescents. The Young-HUNT Study

Abstract: Sleep problems are common among Norwegian adolescents. The strong association between sleep problems and subsequent hospitalization for self-harm could mainly be related to coexistent symptoms of anxiety and depression. Prevention of adolescent sleep problems, anxiety and depression should be targeted when seeking to reduce and prevent self-harm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 41 publications
3
15
0
Order By: Relevance
“…The registration of outcome data has been described in more detail previously [ 10 ]. We registered all self-harm episodes that required hospitalisation from 1 January 1995 to 31 December 2010, based on a list of all acute admissions for persons eligible for Young-HUNT 1, at the two hospitals serving the catchment area for the study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The registration of outcome data has been described in more detail previously [ 10 ]. We registered all self-harm episodes that required hospitalisation from 1 January 1995 to 31 December 2010, based on a list of all acute admissions for persons eligible for Young-HUNT 1, at the two hospitals serving the catchment area for the study.…”
Section: Methodsmentioning
confidence: 99%
“…Also, there is evidence to suggest an association between self-harm risk and drug/alcohol misuse, stressful life events, and socioeconomic disadvantages [ 5 , 8 ]. Sleep problems have been associated with self-harm in two Norwegian studies [ 10 , 11 ]. Motivations for self-harm, and associated predictors are overlapping in different sub-populations and the general population, albeit with some differences.…”
Section: Introductionmentioning
confidence: 99%
“…A handful of longitudinal studies partially supported these findings, where sleep difficulties, and particularly insomnia, predicted later engagement in NSSI (Bandel & Brausch, 2020; Junker, Bjørngaard, Gunnell, & Bjerkeset, 2014; Lundh et al., 2013; Wong et al., 2011). However, this link disappeared when controlling for previous psychopathology (Bandel & Brausch, 2018; Junker et al, 2013). Although informative, these studies have limitations.…”
Section: Introductionmentioning
confidence: 93%
“…Until now, however, few researches have studied the association between sleep duration and NSSI. Previous studies have shown that the close link between sleep problems and self-harm; Di culties initiating sleep, early morning wakening, short sleep duration, severe sleep complaints, daytime sleepiness, and nightmares were associated with increased risk of self-harm in a dose-dependent manner [28,29,54,55]. In this study, we found that, after controlling for potential confounding factors, compared to the weekend catch-up sleeping for 0-1 hours, males who slept < 0 hours or ≥ 3 hours had higher risk of NSSI.…”
Section: Discussionmentioning
confidence: 99%